Estimation of core terrestrial habitat for stream-breeding salamanders and delineation of riparian buffers for protection of biodiversity - Crawford, John A (Conservation biology : the journal of the Society for Conservation Biology, 2007)
Many species of wildlife depend on riparian habitats for various life-history functions (e.g., breeding, foraging, overwintering). Although this unique habitat is critical for many species, delineations of riparian zones and buffers for various taxa are lacking. Typically when buffer zones are determined to mitigate edge effects, they are based on criteria that protect aquatic resources alone and do not consider impacts to wildlife and other terrestrial resources. Using two different survey methods (area-constrained daytime searches and nighttime visual encounter searches), we estimated core terrestrial habitat and buffer widths for stream-breeding salamanders in southern Appalachian streams from May to August 2004. A core terrestrial habitat of 27.0 m encompassed 95% of the salamander assemblage (four species of stream plethodontids), and an additional 50 m (to buffer edge effects) yielded a total buffer of 77.0 m. When each species of the assemblage was analyzed separately, the maximum core terrestrial habitat needed for the Blue Ridge two-lined salamander (Eurycea wilderae), a dominant member and the farthest-ranging species from the stream, was 42.6 m. Thus, we recommend an overall buffer width of 92.6 m in southern Appalachian streams. To protect stream amphibians and other wildlife dependent on riparian areas, land managers and policy makers must consider conserving more than aquatic resources alone. Developing core terrestrial habitat estimates and buffer zone widths for wildlife populations is a critical first step in the conservation of many semiaquatic organisms and protecting biodiversity